Caregivers' knowledge, attitude, and perception toward pneumococcal infection prophylaxis in pediatric sickle cell disease patients in Kumasi, Ghana - Elom Doe; Samuel B. Nguah; Kofi B. Mensah; Kwame O. Buabeng (Health Science Reports, 2023)
Abstract Background and Aims Pneumococcal infection prophylaxis (PIP) is necessary for children with sickle cell disease (SCD) due to the enhanced risk of pneumococcal infections and associated mortalities. PIP measures include periodic administration of pneumococcal conjugate vaccine (PCV), twice‐daily administration of phenoxymethylpenicillin tablets, and nonpharmacological measures. This work assessed the attitude, knowledge, and perception of parents of SCD children on PIP, how parents obtain phenoxymethylpenicillin, and their preference for PIP. Methods This prospective cross‐sectional study involved 200 parents of SCD children between 2 and 12 years old seeking medical care at the SCD clinic of the Komfo Anokye Teaching Hospital, Ghana. Infants involved had hemoglobin SS, SC, or S‐βthal. A survey questionnaire (written) was administered to gather and interpret the data using Statistical Package for Social Sciences version 25 software. Results Out of 200 respondents in this study, 12% knew vaccination could prevent pneumococcal disease, but only 4% had heard about PCV, 96% had heard about phenoxymethylpenicillin tablets, and 40% knew it could prevent it. Although phenoxymethylpenicillin is reimbursed on national insurance, 87% obtained the tablets from outside the hospital with cash, whereas 12% obtained the tablets from the hospital either on insurance or with cash. About 38% mentioned that they had discontinued treatment with tablets due to intentional withdrawal, lack of funds, noncompliant children, and running out of medicine. All but 2% of respondents said they would prefer vaccines to tablets. Conclusion There is a significant shortfall in knowledge, attitude, and perception of parents of SCD children concerning PIP, which warrants education and awareness creation on PIP in sickle cell clinics to ensure optimum clinical and health outcomes and reduce morbidity and mortality related to such infections.